Bartonella koehlerae sp. nov., Isolated from Cats - Droz, Sara (American Society for Microbiology, 1999)
Two of the 25 Bartonella isolates recovered during a prevalence study of Bartonella henselae bacteremia in domestic cats from the greater San Francisco Bay region were found to differ phenotypically and genotypically from all prior B. henselae isolates. These isolates, C-29 and C-30, which were recovered from the blood of two pet cats belonging to the same household, grew on chocolate agar as pinpoint colonies following 14 days of incubation at 35°C in a candle jar but failed to grow on heart infusion agar supplemented with 5% rabbit blood. Additional phenotypic characteristics distinguished the isolates C-29 and C-30 from other feline B. henselae isolates. The restriction patterns obtained for C-29 and C-30 by citrate synthase PCR-restriction fragment length polymorphism (RFLP) analysis as well as by genomic RFLP could not be distinguished from each other but were distinctly different from that of the B. henselae type strain. In reciprocal reactions, DNAs from strains C-29 and C-30 were 97 to 100% related under optimal and stringent DNA reassociation conditions, with 0 to 0.5% divergence within related sequences. Labeled DNA from the type strain of B. henselae was 61 to 65% related to unlabeled DNAs from strains C-29 and C-30 in 55°C reactions, with 5.0 to 5.5% divergence within the related sequences, and 31 to 41% related in stringent, 70°C reactions. In reciprocal reactions, labeled DNAs from strains C-29 and C-30 were 68 to 92% related to those of the B. henselae type strain and other B. henselae strains, with 5 to 7% divergence. The 16S rRNA gene sequence of strain C-29 was 99.54% homologous to that of the type strain of B. henselae. On the basis of these findings, the two isolates C-29 and C-30 are designated a new species of Bartonella, for which we propose the name Bartonella koehlerae. The type strain of Bartonella koehlerae is strain C-29 (ATCC 700693).